Ninja - Weldon, Les.; Lerner, Danny; Davidson, Boaz, 1943-; Hurst, Michael, 1973-; Florentine, Isaac; Adkins, Scott, 1976-; Ihara, Tsuyoshi; Hiji, Mika.; Jensen, Todd.; Hagon, Garrick; Igawa, Togo.; Edwards, Steve; et al. ([California] : First Look Studios, 2009)
The deadly weapons of the last Koga Ninja have now been entrusted to an American Ninjutsu student studying in Japan. Commanded by his Sensei to return to New York and protect the weapons at all cost, he must defeat the skilled Yakuza assassins hunting him and prevent the power of the weapons from falling into evil hands.
Title from container.
Originally produced as a motion picture in 2009.
Special features: Previews.
Director of photography, Ross Clarkson ; edited by Irit Raz ; music by Steve Edwards ; martial arts consultant, Fumio Demura ; fight choreography, Akahiro "Yuji" Noguchi.
Scott Adkins, Tsuyoshi Ihara, Mika Hijii, Todd Jensen, Garrick Hagon, Togo Igawa.
MPAA rating: R.
Keywords: Ninjutsu -- Japan -- Drama; Ninjutsu weapons -- New York (State) -- New York -- Drama; Yakuza -- New York (State) -- New York -- Drama; Attempted assassination -- New York (State) -- New York -- Drama; Good and evil -- Drama; Ninjutsu -- Japn̤ -- Teatro; Armas -- Nueva York (Estados Unidos : Estado) -- Nueva York -- Teatro; Martial arts films; Action and adventure films; Video recordings for the hearing impaired; Feature films; Fiction films